City-Tour München. Wachsende Stadt gestalten - eine Reflexion. - Förster, Agnes; Thierstein, Alain (Routledge, 2017)
Der Beitrag reflektiert die Stadtentwicklungspolitik Münchens vor dem Hintergrund, eine wachsende Stadt bei nur noch geringen Flächenreserven zu gestalten. Er beschreibt die Handlungsstrategien langfristiger Siedlungsentwicklung (LaSie), die Strategie der Nachverdichtung, Umstrukturierung von Wohnen und Arbeiten, Stadterweiterungen auf vier Feldern des Lernens: Strategie, Instrumente, Kommunikation, Stadtgesellschaft.

The city and metropolitan region of Munich is facing continuing growth in employment and population. The city of Munich alone is expected to have 300 000 new inhabitants by the year 2035, and the larger planning region an additional 400 000 new inhabitants. Since the 1990s urban development in Munich - following the main city's strategy compact, urban, green - has focused on brownfield development, mainly former military barracks and railway yards. Today, available land within the existing land-use plan has become scarce. Consequently, the city of Munich launched the Long-term Settlement Development project in 2009. Their main strategies - densification, transformation of industrial land, and enlargement of land use at the city's municipal borders - were supposed to activate sites for housing as well as for highly mixed-use urban areas for the next five to 25 years. Eight years after the launch of that strategy, an intermediate assessment is due. Each one of the three strategies shows a specific combination of challenges for further urban development. First, densification takes place in existing neighborhoods, where people feel highly affected by densification projects. It is therefore crucial to organize a process of give and take between existing and new inhabitants, and their respective spatial demands. Second, transformation of derelict industrial sites has turned out to be a process that involves a so far unusual multitude of actors, where municipal authorities are but one voice in a concert of property owners, new companies, real estate investors, and other potential users. Within the strategy of increasing usable land in the land-use plan, the traditional public logic of managing large-scale urban projects confronts the restraints of partisan political interests and a related hesitancy in committing the city to balanced long-term development.
Keywords: Stadtentwicklungsplanung; Siedlungsentwicklung; Stadterweiterung; Stadtwachstum; Dichte; Planung; Kommunikation; Nachverdichtung; Stadtgesellschaft